(untitled) - Gauwitz, Donna F. (New York, 2009)
Administering Medications: Pharmacology for Healthcare Professionals is designed to teach the safe administration of medications to healthcare students entering nursing, medical assisting, and other allied healthcare professions. This textbook speaks directly to students and encourages students to identify and apply the concepts learned. The organization of the chapters allows students and instructors to build a knowledge base that starts with the fundamentals of medication administration and progresses through the drugs frequently used to treat most common diseases. Most chapters are organized around a body system to help students fully understand drug actions. For easy identification, the 50 most frequently prescribed drugs are boldfaced in the Representative Drug table at the end of most chapters. The Patient Education, Healthcare for Today and Tomorrow, and Legal and Ethical Issues boxes continue to be highlighted features in this edition. The Patient Education boxes contain important information for the healthcare professional to communicate to the patient. This feature also includes cultural diversity and pediatric and geriatric implications where appropriate. The Healthcare for Today and Tomorrow boxes alert the healthcare professional to issues or problems that may be encountered today or in the future. The Legal and Ethical Issues boxes illustrate the role of the healthcare professional in actual legal and ethical situations pertinent to the content of each chapter.
Keywords: Pharmaceutical Preparations,Chế phẩm dược phẩm; Administration & dosage,Quản lý và liệu lượng